Perception of congruence between music and movement in a rhythmic gymnastics routine - Loo, Fung Chiat; Loo, Fung Ying; Chua, Yan Piaw (TextRoad Publication, 2013)
For sports that involve a routine or choreography, music is used either as a background sonic accompaniment or to enhance and synchronize the movement of the athletes. This paper aims to investigate the perception of congruence between movements and music in a rhythmic gymnastics routine from a musical perspective. Contrary to the conventional method of choreographing a routine based on selected music, this research aims to investigate the quality of the routine with existing choreography accompanied by a newly-composed music. A routine performed by a gymnast was recorded and music composed to match the existing choreography based on the recording. Fifty-two participants from a tertiary institution, all music majors, were asked to evaluate two videos which had the same rhythmic gymnastics routine, one with the athlete’s original music and the other edited with the new music. The result shows that a significantly higher percentage of respondents chose the new accompaniment as having better congruence between the music and movement. Most of the respondents also perceived the new composition to be the original music used by the gymnast.